The promise and challenges of cell therapy for psoriasis. (1st November 2021) - Lwin, S.M.; Snowden, J.A.; Griffiths, C.E.M.
Summary: The management of moderate‐to‐severe psoriasis has been transformed by the introduction of biological therapies. These medicines, particularly those targeting interleukin (IL)‐17 and IL‐23p19, can offer clear or nearly clear skin for the majority of patients with psoriasis, with good long‐term drug survival. However, as currently used, none of these therapies is curative and disconcertingly there is a small but increasing number of patients with severe psoriasis who have failed all currently available therapeutic modalities. A similar scenario has occurred in other immune‐mediated inflammatory diseases (IMIDs) where treatment options are limited in severely affected patients. In these cases, cell therapy, including haematopoietic stem cell transplantation (HSCT) and mesenchymal stromal cells (MSC), has been utilized. This review discusses the various forms of cell therapy currently available, their utility in the management of IMIDs and emerging evidence for efficacy in severe psoriasis that is unresponsive to biological therapy. Balancing the risks and benefits of treatment vs. the underlying disease is key; cell therapy carries significant risks, costs, regulation and other complexities, which must be justified by outcomes. Although HSCT has anecdotally been reported to benefit severe psoriasis, sometimes with apparent cure, this has mainly been in the setting of other coincidental 'routine' indications. In psoriasis, cell therapies, such as MSC and regulatory T cells, with a lower risk of complications are likely to be more appropriate. Well‐designed controlled trials coupled with mechanistic studies are warranted if advanced cell therapies are to be developed and delivered as a realistic option for severe psoriasis.